Sample preparation for thermo-gravimetric determination and thermo-gravimetric characterization of refuse derived fuel. (February 2016) - Robinson, T.; Bronson, B.; Gogolek, P.; Mehrani, P.
Highlights: Preparation of refuse derived fuel (RDF) sample was explored. Preparation methods were related to the results of thermo-gravimetric analysis (TGA). Analysis of 10 mg RDF samples by TGA was repeatable when samples were prepared by cryogenic milling. With cryogenic milling, TGA could compete with AMS for determining RDF renewability. With cryogenic milling, TGA could compete with selective dissolution for RDF renewability analysis. Abstract: Thermo-gravimetric analysis (TGA) is a useful method for characterizing fuels. In the past it has been applied to the study of refuse derived fuel (RDF) and related materials. However, the heterogeneity of RDF makes the preparation of small representative samples very difficult and this difficulty has limited the effectiveness of TGA for characterization of RDF. A TGA method was applied to a variety of materials prepared from a commercially available RDF using a variety of procedures. Applicability of TGA method to the determination of the renewable content of RDF was considered. Cryogenic ball milling was found to be an effective means of preparing RDF samples for TGA. When combined with an effective sample preparation, TGA could be used as an alternative method for assessing the renewable content of RDF.